PROBLEMATIKA PELAKSANAAN PUTUSAN ARBITRASE INTERNASIONAL DI INDONESIA (Kajian Terhadap Konsep Keadilan Dalam Perspektif Filsafat Hukum Dan Filsafat Hukum Islam) - dewi, ayu atika (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2017)
The international arbitration awards are basically final and binding. By its nature international arbitration award should has the power of self execution. However, the nature is not absolute because it is still open certain legal efforts. The existence of such legal effort causes the arbitral award not necessarily to be directly executed. This study aims to find out how the problematic of the implementation of international arbitration decision when viewed from the concept of justice in the perspective of legal philosophy and philosophy of Islamic law. The research is analytical descriptive with normative juridical approach and data obtained through library research. This research concluded that the implementation of international arbitration award faced with many obstacles causing delay of execution of the decision. As is known the purpose of the parties to choose arbitration institution as a dispute settlement forum is to get justice. However, if viewed from the perspective of legal philosophy, the enforcement of international arbitration rulings is not in line with the expected goal is to achieve justice. In line with that, the purpose of law in Islamic law perspective to realize kemashlahatan also can not be obtained by the parties. Due to the failure of the execution process, the search for justice or kemashlahatan also failed to execute. Keywords: international arbitration award, justice.